Hot Deformation Characteristics and Dynamic Recrystallization Mechanisms of a Novel Nickel‐Based Superalloy. Issue 12 (2nd August 2020) - Lv, Shaomin; Jia, Chonglin; He, Xinbo; Wan, Zhipeng; Li, Yang; Qu, Xuanhui
Abstract : The hot deformation characteristics of a novel nickel‐based superalloy is investigated via the isothermal compression test in temperature range of 1000–1150 °C and strain rate of 0.001–10 s −1 under the true strain of 0.8. The hot deformation characteristics of GH4065 alloy are studied here for the first time. Based on the flow stress data, it is observed the typical features of flow curves exhibit the occurrence of dynamic recrystallization (DRX) during the hot deformation process. The constitutive equation in the Arrhenius‐type model is established, and activation energy ( Q ) is determined as 844.787 kJ mol −1 . The microstructure evolution and DRX mechanism are investigated by electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) technique. The results reveal that the fraction of low angle grain boundaries (LAGBs) decrease gradually with the increase in deformation temperature, whereas the fraction of Σ3 boundaries increase first and then decrease. For γ + γ ′ dual‐phase region, the particle‐induced DRX (PIDRX), characterized by the generation of sub‐grains accelerated by γ ′ precipitates pinning dislocations, and discontinuous dynamic recrystallization (DDRX) are the dominant nucleation mechanism of DRX. For γ quasi‐phase region and γ single‐phase region, the occurrence of bulged grain boundaries with twins further illustrates that DDRX plays a more significant role. Abstract : The hot deformation characteristics and dynamic recrystallization (DRX) mechanisms of GH4065 alloy are investigated for the first time. The discontinuous dynamic recrystallization (DDRX) becomes the more dominant mechanism with the deformation temperature increasing. The particle‐induced DRX (PIDRX) take place at the γ + γ′ dual‐phase region, which is characterized by γ′ precipitates by inducing the generation and rotation of sub‐grains.